A barragem romana de Alfundão (Ferreira do Alentejo) - Cardoso, João Luís (2016)
Architectural characterization and interpretation of the remains of a Roman dam, identified near a villa, in Vilares de AIfundão (Ferreiro do Alentejo, Beja). A comparative study of the dam' s construction - small water-retaining infrastructures for agriculture purposes.